Quality of life in patients with epilepsy - Dorrego Pamela; Joneret Gisele; Zofiaurre Jennifer; Perez Armanazco Cinthia; Morales David; Arrigoni Maria Isabel (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2018)
Introduction: Epilepsy affects health globally and reduces the quality of life of those who suffer from it.  Objectives: To analyze the quality of life in adult patients diagnosed with epilepsy. Methods: An observational, descriptive, cross-sectional study was carried out. The QOLIE-31 questionnaire was applied to all the included patients. Results: 30 patients, 17 men and 13 women participated. 73.3% (n = 22) of the patients had a history of epilepsy greater than 5 years. 43.3% of the patients presented poor quality of life. The factor that generates the greatest impact on the quality of life of these patients is the side effect of antiepileptic drugs. The patients who perceived having a better quality of life are those who were treated with monotherapy, especially levetiracetam. Conclusion: Patients with epilepsy require a multidisciplinary management, whose objective is not only to achieve total control of the crisis, but also that the patient has the tools to overcome daily the impact that this disease generates on their quality of life.